POST-HARVEST EFFECTS OF VARIOUS EDIBLE COATINGS ON SHELF LIFE AND QUALITY OF BITTER GOURD - AYUB, A; ANEES, M; ANJUM, S; MAQSOOD, S; ABBAS, T; SAFDAR, H; ASHRAF, MI; SARWAR, M; AHMAD, W (Biological and Clinical Sciences Research Journal, 2024)
Due to various factors, including fungal infection, tissue weakening, yellowing, and mass reduction, bitter gourds are susceptible to postharvest losses, particularly when stored at room temperature. To preserve their quality, bitter gourds undergo several treatments during the postharvest stage. The research was designed to determine the effects of several edible coatings on the shelf life and quality of bitter gourd at room temperature. These coatings included Aloe Vera Gel extract, Neem leaf extract, Garlic extract, Ginger extract, and lemongrass leaf extract. Due to various factors, including fungal infection, tissue weakening, yellowing, and mass reduction, bitter gourds are susceptible to postharvest losses, particularly when stored at room temperature. To preserve their quality, bitter gourds undergo several technical treatments during the postharvest. The study was carried out to determine the effects of several edible coatings on the shelf life and quality of bitter gourd at room temperature. These coatings included Aloe Vera Gel extract, Neem leaf extract, Garlic extract, Ginger extract, and Lemongrass leaf extract. The findings showed that the postharvest quality and shelf life of bitter gourd were strongly impacted by edible coating. Coated bitter gourds showed a significant response in weight loss, extended shelf life and visual quality, and postponed color changes or yellowing after 8 days of storage. Furthermore, pH, TSS, titratable acidity, and ash contents respond better than non-treated fruits. These findings were verified by two-factor factorial ANOVA, and LSD examination was implemented to assess the outcomes with a probability of five percent level.